Simultaneous determination of Simvastatin and Sitagliptin in tablets by new univariate spectrophotometric and multivariate factor based methods - Lotfy, Hayam Mahmoud; Hegazy, Maha Abdel Monem; Abdel-Gawad, Sherif Abdel Naby (European Journal of Chemistry, 2013)
Five simple, sensitive and precise spectrophotometric and chemometric methods were used for simultaneous determination of Simvastatin (SM) and Sitagliptin (SIT) in their pure powdered forms and in the tablets. The proposed methods are the extended ratio subtraction method (EXRSM), ratio difference method (RDSM), mean centering of ratio spectra method (MCR) and chemometric methods, namely principal component regression (PCR) and partial least squares (PLS). In EXRSM; SM was determined at 237.5 nm, while SIT was determined at 267 nm, in RDSM; the difference in amplitudes at 237.5 and 245.5 nm was used for SM and 263.5 and 248.0 nm for SIT, while in MCR; SM and SIT were determined at 239.0 and 273.0 nm, respectively. PCR and PLS are factor based multivariate methods which utilize the whole spectra of SM and SIT. The developed methods were successfully applied for the determination of the studied drugs in their bulk powder, laboratory prepared mixtures and in tablets. All validation parameters of the developed methods were determined. The obtained results were statistically compared with each other along with a reported method.